1993
DOI: 10.1002/app.1993.070490410
|View full text |Cite
|
Sign up to set email alerts
|

Batch polymerization of methyl methacrylate in mini/macroemulsions

Abstract: SYNOPSISThe kinetics of the isothermal batch macroemulsion and miniemulsion polymerizations of methy1 methacrylate (MMA) at 50°C have been studied. Hexadecane was used as the cosurfactant or swelling agent. The nucleation mechanisms were observed to be different between macroemulsions and miniemulsions. The effect of surfactant, cosurfactant, initiator, shear, and hold time on droplet nucleation was studied. The miniemulsion particles were found to contain more radicals on average than the macroemulsion partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
1
1

Year Published

1996
1996
2006
2006

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(66 citation statements)
references
References 16 publications
2
62
1
1
Order By: Relevance
“…If this is the case, the end of the nucleation should be about 20% conversion. This would be consistent with the results found by Chamberlain et al 10 and Fontenot et al, 28 while according to the number of particles obtained during the polymerization (Fig. 5), it seems that the end of nucleation in this system should be around 60% conversion.…”
Section: Particle Size and Its Distribution During Polymerizationsupporting
confidence: 89%
“…If this is the case, the end of the nucleation should be about 20% conversion. This would be consistent with the results found by Chamberlain et al 10 and Fontenot et al, 28 while according to the number of particles obtained during the polymerization (Fig. 5), it seems that the end of nucleation in this system should be around 60% conversion.…”
Section: Particle Size and Its Distribution During Polymerizationsupporting
confidence: 89%
“…Also, we can deduce that the nucleation period lasts to a monomer conversion of 40 -60%. It is coincident with the results observed by Miller et al 37 but discordant with the results observed by Fontenot and Schork 12 and Chamberlain et al 38 in the St miniemulsion polymerization initiated by KPS. They found that the nucleation period lasts to 10 -30% of the conversion.…”
Section: Polymerization Of Miniemulsionsupporting
confidence: 82%
“…Furthermore, the value x ¼ 0:41 is much larger than 0.11 and 0.28 for the miniemulsion and emulsion polymerization of MMA. 42 On the contrary, x NMEP ¼ 0:14 is between 0.11 and 0.28. Delgado et al 3 found the opposite relationship in his copolymerization work with vinyl acetate and butyl acrylate.…”
Section: Colloidal and Molecular Weight Parametersmentioning
confidence: 99%